Jean Jaurès : The Inner Life of Social Democracy - Kurtz, Geoffrey, 1974- (Book collections on Project MUSE., 2014)
"A study in social democratic political theory that examines the writings of Jean Jaures (1859-1914), the parliamentary and philosophical leader of French socialism"--Provided by publisher.